Application of South African VAT on e-commerce transactions - Xaba, Nduduzo Justified (My University, 2017)
The present study sought to investigate self-selection among internal and international migrants in Gauteng by making use of the Gauteng City Region Quality of Life Survey data. The present study also sought to disentangle the effects of observed and unobserved characteristics in the self-selection of migrants by conducting Oaxaca-Blinder decomposition on overall employment and self-employment outcome variables. Preliminary descriptive statistics indicated that international migrants experienced markedly higher levels of employment than both locals and internal migrants driven by higher rates of informal and self-employment. System GMM analysis of pseudo panel data confirmed these results and showed that international migrants had a higher probability of employment and self-employment. Oaxaca Blinder decomposition indicated that unobserved characteristics explained the greatest share of the differences in the rates employment and self-employment of locals, internal migrants and international migrants. These results provide evidence for the positive selection of international migrants to Gauteng on unobservable characteristics relevant to the region’s labour market. Key Words Self-Selection; Migration; Self-Employment; Employment
A research report to be submitted to the Faculty of Commerce, Law and Management, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce( Specialising in Taxation); March 2016
Keywords: Self-Selection; Migration; Self-Employment; Employment; UCTD; Value-added tax--South Africa; Taxation--South Africa; Electronic commerce--South Africa; SDG-8: Decent work and economic growth